2019
DOI: 10.1182/blood-2018-10-877563
|View full text |Cite
|
Sign up to set email alerts
|

The BRISC deubiquitinating enzyme complex limits hematopoietic stem cell expansion by regulating JAK2 K63-ubiquitination

Abstract: Hematopoietic stem cell (HSC) homeostasis is controlled by cytokine receptor–mediated Janus kinase 2 (JAK2) signaling. We previously found that JAK2 is promptly ubiquitinated upon cytokine stimulation. Whether a competing JAK2 deubiquitination activity exists is unknown. LNK is an essential adaptor protein that constrains HSC expansion through dampening thrombopoietin (TPO)–induced JAK2 signaling. We show here that a LNK-associated lysine-63 (K63)–deubiquitinating enzyme complex, Brcc36 isopeptidase complex (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…The candidates were chosen from the literature based on the following criteria: (1) the knockout increased the repopulating capacity of HSCs, (2) the knockout enhanced HSC frequency and self-renewal, and (3) the knockout did not cause tumorigenesis in serial transplantations. Based on these criteria, we chose 10 candidate genes, namely Lnk [ 21 , 28 , 29 ], p18Ink4c ( p18 ) [ 30 , 31 ], Mapk14 ( p38 ) [ 32 ], Egr1 [ 33 ], Ikkb [ 34 ], p190-B ( p190 ) [ 35 ], Merit40 ( M40 ) [ 36 , 37 , 38 ], Gli1 [ 39 ], c-Cbl ( Cbl ) [ 20 ], and GzmB [ 40 ]. Prior to the screen, each sgRNA of the library was independently tested in a fluorescent reporter assay for on-target cleavage activity ( Figure S1a–c ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The candidates were chosen from the literature based on the following criteria: (1) the knockout increased the repopulating capacity of HSCs, (2) the knockout enhanced HSC frequency and self-renewal, and (3) the knockout did not cause tumorigenesis in serial transplantations. Based on these criteria, we chose 10 candidate genes, namely Lnk [ 21 , 28 , 29 ], p18Ink4c ( p18 ) [ 30 , 31 ], Mapk14 ( p38 ) [ 32 ], Egr1 [ 33 ], Ikkb [ 34 ], p190-B ( p190 ) [ 35 ], Merit40 ( M40 ) [ 36 , 37 , 38 ], Gli1 [ 39 ], c-Cbl ( Cbl ) [ 20 ], and GzmB [ 40 ]. Prior to the screen, each sgRNA of the library was independently tested in a fluorescent reporter assay for on-target cleavage activity ( Figure S1a–c ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to p38, Lnk and Cbl are known inhibitors of Tpo and c-Kit signaling in HSPCs, which play important roles in HSC self-renewal [ 21 ]. The inhibition of Lnk and Cbl enhances the sensitivity towards Tpo and stem cell factor, the c-Kit ligand, and results in an increased frequency of HSCs [ 20 , 36 , 38 , 48 , 49 ]. As the mechanism is different between p38 and Lnk / Cbl , we hypothesize that a combination may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…The hematopoietic cells of LNK-knockout mice were highly sensitive to a series of cytokines, including IL-3, IL-7, EPO, and TPO [25]. As a result, the JAK/STAT and ERK/MAPK pathways are highly activated [9,10]. Mice with LNK deficiency exhibited hematopoietic disorders, including a triple increase in circulating white blood cell and platelet levels, the accumulation of immature B cells in bone marrow and spleen, and the expansion of hematopoietic stem cell pools with an enhanced self-renewal ability via the JAK2 pathway [19].…”
Section: Discussionmentioning
confidence: 99%
“…It contains a pleckstrin homology (PH) domain and a Src homology 2 (SH2) domain that specifically bind to phosphorylated tyrosine residues, which mediates signal transduction, and an N-terminal prolinerich region that mediates dimerization [8,9]. Studies have shown that LNK can inhibit wild-type or mutant JAK2 signal transduction through the SH2 domain and inhibit the activation of the JAK/STAT, ERK/MAPK, and PI3K/Akt/mTOR/GSK3β pathways [9][10][11][12][13]. Clinical studies have found that LNK mutations can lead to diabetes, heart disease, kidney injury, autoimmune hepatitis, acute lymphocytic leukemia, and bone marrow proliferative malignancies [6,[13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…G-CSF induces tyrosine phosphorylation of JAK2 through G-CSFR which leads to enhanced proliferation [45]. Of note, in a very recent study by Donaghy et al BRCC3-mediated deubiquitination of JAK2 has been implicated in limiting hematopoietic stem cell expansion and knockdown of BRCC3 was associated with an increased K63-ubiquitination and activation of JAK2 [46]. Therefore, BRCC3 inactivation enhances JAK2 signaling by two mechanisms.…”
Section: Discussionmentioning
confidence: 99%